Managing HBV/HIV coinfection: from diagnostics to long-acting antiretroviral therapy - Raczyńska, Aleksandra; Lara, Martyna; Ruszecka, Anna; Dręczewski, Marcin; Jaroszewicz, Jerzy (Clinical and Experimental Hepatology, 2026)
Hepatitis B virus (HBV) and human immunodeficiency virus (HIV) coinfection accelerates liver disease progression and increases the risk of hepatocellular carcinoma (HCC). Lifelong HBV-active antiretroviral therapy is the cornerstone of management, while occult HBV infection and isolated anti-HBc serology require careful monitoring, particularly when switching to long-acting regimens lacking HBV activity. Comprehensive diagnostics, including HBV DNA testing, fibrosis assessment, and evaluation of serological profiles, are essential for optimal care. Vaccination with next-generation HBV vaccines (ex. CpG adjuvant, multiantigenic), provides superior immunogenicity and should be prioritized in people living with HIV, especially in prior nonresponders. Regular HCC screening is recommended in individuals with advanced liver disease to enable early detection and intervention. This review summarizes current evidence on diagnostics, therapy, vaccination, monitoring, and cancer prevention, providing practical recommendations to improve outcomes in HIV/HBV coinfected populations.